As unidades geomorfológicas e a erosão acelerada na bacia do Ribeirão Estiva. Uberlândia. MG - Pereira, Kátia Gisele de Oliveira (2001)
Soil erosion can be under stood as being a result of environmental conditioning in addition to soil and climatic conditions as well as taking into consideration socio-cultural variables involved in its use. The research conducted offers information pertaining to environmental characteristics associated with erosion and regional character is tics were initially examined. Subsequently, significant character is tics of the Ribeirão Estiva basin were identified, providing a framework for reference of its contours (shape) which were classified in the following geomorphological unit s: Elevations (summits) with fissures ( in staggered format ion) and steep slopes ; slopes with assorted levels of fissures ; gent le slopes and alluvial plains for which the advancing process of erosion was identified. The information obtained was classified based on bibliographic research of thematic mapping of field studies and soil analysis with the goal of defining environmental processes of erosion. This explanation of erosion processes may be useful in the management of hydrographic basins and as a resource for students studying this phenomenon. In addition, it will provide useful information for resident s of Miraporanga District and Ribeirão Estiva basin.